Validity of estimating muscle and fat volume from a single MRI section in older adults with sarcopenia and sarcopenic obesity. Issue 5 (May 2017) - Yang, Y.X.; Chong, M.S.; Lim, W.S.; Tay, L.; Yew, S.; Yeo, A.; Tan, C.H.
Abstract : Aim: To determine if there is a correlation between the cross-sectional areas (CSAs) in a single section and the volumes of muscles and fat in the thigh of sarcopenic and sarcopenic obesity (SO) populations using magnetic resonance imaging (MRI), and to assess the correlation between thigh MRI data and patient health status, i.e., normal, obese, sarcopenia, and SO. Materials and methods: One hundred and ninety community-dwelling older adults were recruited and categorised into four subgroups based on Asian established criteria: normal, obese, sarcopenia, and SO. MRI images were acquired and muscles, subcutaneous fat (SF), and intermuscular fat (IMF) were automatically segmented in the thighs. Volumes of muscles and fat were calculated for the middle third of the thigh, while CSAs were assessed using a single section at 50% femur length. Results: Correlation between CSA and volume were significantly high ( p <0.001) for all components of muscle (0.907), SF (0.963), and IMF (0.939). Thigh CSA and volume both correlated significantly with a clinical diagnosis of normal, obesity, sarcopenia, and SO ( p <0.03). Conclusions: A single CSA at 50% of femur length yields good estimation of muscle and fat volume in the thighs of older adults and correlates closely with the clinical criteria for sarcopenia and SO. This has the potential to greatly reduce costs, scan time, and post-processing time in clinical practice for the prediction of these conditions. Highlights: Correlation between CSA and volume were significantly high for thigh components. Thigh CSA correlated closely with sarcopenia and sarcopenic obesity. Cost and time could be reduced in clinical practice by single slice measurements.